Multislice computed tomography of potential liver donors - Timur Sarsengaliyev; Boris Tsoy; Elmira Chuvakova (National Scientific Medical Center, 2017)
Objective: Multislice computed tomography (MSCT) prior to liver transplantation is an important aspect of the diagnosis of changes in the liver as fat infltration, as well as visualization of the individual vascular anatomy and calculation of liver volume. The aim of our study was to analyze the results of the single center experience to conduct liver MSCT of donors who are preparing for the transplant donation. Methods: We studied the MSCT evaluation results of 39 (25 male and 14 female) potential liver donors' during the 2015 - 2016 years. Liver MSCT with various standard renovations were used for more detailed visualization of blood vessels in each liver segment. Images were obtained on 64-slice MSCT (Aquilion; Toshiba Medical Systems, Tokyo, Japan). Interpretation of the results provided in accordance with embodiments of origin of the hepatic artery, portal vein anatomy and drainage of the hepatic veins. Results: The main results of the anatomy of the hepatic artery, portal and hepatic veins are shown in Table 1, 2, 3. Based on the MSCT of 39 donor's liver, 24 donors were identifed as appropriate for donation. 15 donors were contraindicated for donation due to: in 8 - were signs of fatty infltration, 2 donors - vascular anomaly of the portal vein, benign growths were detected in 5 donors. Conclusion: MSCT is a primary diagnostic method for the preoperative planning of surgical resection of the liver, as well as preliminary identifcation of hepatic pathology. According to the results and experience of our center, in 61.5% cases, liver donors were selected for donation and remaining 38.5% of the donors were excluded from organ donation, in connection with the identifed contraindications.